PENGARUH GAMBAR VISUAL PERINGATAN KESEHATAN PADA KEMASAN ROKOK TERHADAP MINAT BELI KONSUMEN ROKOK - Rahmat Purbandono Hardani; Kurniawan Kurniawan (Jurnal Ekonomi Dan Bisnis, 2022)
Smoking has become a normal activity for the community. At any time, it is very easy to find people who have smoking habits from all walks of life and even ages. Cigarettes are getting easier to find because nowadays cigarettes are easy to get in every shop, even small stalls. Cigarettes are the result of processed tobacco which is unhealthy for consumption, the use of cigarettes is smoked and emits smoke from the mouth using a filter which has many toxic substances in it which are not good for human health. The government is trying to control the spread and public interest in smoking through visual appeals on cigarette packages. Based on the test results, the use of visual images to make smokers aware of the dangers of smoking is effective.